SURVIVAL RATES IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS: REGIONAL REGISTRY DATA - R. R. Ismagilova; E. S. Zamanova; A. N. Maksudova (Научно-практическая ревматология)
There has been an increase in the survival rates of patients with systemic lupus erythematosus (SLE) in recent decades.Objective: to determine the survival rates of SLE patients in the Republic of Tatarstan.Subjects and methods. The records of SLE inpatients treated at the Nephrology and Rheumatology Departments of the Republican Clinical Hospital in 2004 to 2018 were retrospectively analyzed. Demographic data (gender, age at onset of the first signs of the disease, age at diagnosis of SLE, its duration, labor activity, and disability), clinical manifestations of the disease (damage to the  musculoskeletal system, skin and mucous membranes, kidneys, as well as serositis, neuropsychological disorders), and 5-, 10- and 15-year survival rates were analyzed. A hierarchical cluster analysis was used to group patients on the basis of the similarity in the measured characteristics.Results and discussion. A total of 256 SLE patients (230 females and 26 males) were followed up. The median age at onset of the first symptoms of the disease for females and males was 29.0 [21.0; 38.0] and 25.5 [18.0; 37.0] years, respectively; the age at SLE diagnosis was 30.0 [23.0; 41.0] and 25.5 [18.0; 37.0] years. The main clinical manifestations of the disease were damages to the musculoskeletal system (n=199 (77%)), skin and mucous membranes (n=168 (66%)), and kidneys (n=155 (61%)), neurological disorders (n=39 (15%)) and serositis (n=83 (32%)). In the above period, 29 patients died in the study group; there are no data on 10 patients. The 5-, 10-, and 15-year survival rates of patients in our group were 93.7, 90.8, and 86.4%, respectively; those in patients with lupus nephritis (LN) were 90.4, 86.6, and 82.1%; those in hypertensive patients were 89.5, 84.6, and 79.3%. A cluster analysis identified four clusters. The most important criteria for grouping the patients into clusters were the presence of antiphospholipid syndrome (APS), LN, and hypertension. Cluster 1 included patients with LN and hypertension; Cluster 2 comprised those with APS, LN, and hypertension. Cluster 3 consisted of patients having hypertension only; Cluster 4 included those with LN only. In Cluster 2, the 10- and 15-year patient survival rates decreased to 77.9 and 70.1%, respectively.Conclusion. In our study, 5-, 10-, and 15-year patient survival rates were 93.7, 90.8, and 86.4%, respectively. Gender and age at SLE diagnosis did not affect death rates. The risk of death was significantly higher in patients with LN and hypertension.